The West African Craton - (:unkn) unknown (My University, 2024)
The 3,000 km long and 2,000 km wide West African Craton exposed as the Leo-Man Shield in the south and the Reguibat Shield in the north, covered by Taoudeni, Iullemeden, and Volta basins, represents one of the largest outcrops of Precambrian orogens worldwide. Based on a review of published geophysical, petrological, geochemical, geochronological, structural, metamorphic, and metallogenic data, we propose an evolving geodynamic scenario covering the period from the Archean (~3.5 Ga) until the Mesozoic (~90 Ma). The Archean domains of both the Leo-Man and Reguibat shield (~3.5-2.6 Ga) are predominantly built of high-grade gneisses and magmatic rocks interpreted as resulting from hot-Earth geodynamic processes. The Paleoproterozoic domains (~2.35-1.9 Ga) are built of juvenile volcanic rocks with some zones (e.g., eastern Ghana, boundaries between the Archean and Paleoproterozoic domains), which show isotopic and geophysical signatures of reworked Archean crust. A large amount of data suggest a transitional plate tectonics setting characterized by volcanic arcs, cold metamorphic gradients, and rapid burial and exhumation of supracrustal rocks, important changes in orientation of stress field during the Eburnean orogeny as well as the occurrence of metal deposits characteristic for volcanic arc settings. However, some characteristics of hot orogens documenting the transitional character were also revealed: the greenstone-tonalite-trondhjemite-granodiorite-like granitoid domains, deep-seated subvertical craton-scale network of shear zones post-dating the principal accretion period, or the absence of ultrahigh-pressure metamorphism. The Pan-African orogenic belts (~0.8-0.58 Ga) surrounding the West African Craton show clear evidence of subduction/continental collision geodynamic setting. After the Pan-African orogeny, only local mantle-derived magmatism crosscutting older crust was reported in a form of doleritic dykes, kimberlite diatremes, and alkaline int
Keywords: African Research